Predicting critical thinking through computer and analytical literacy with the moderating role of gender - Rozita Deravipor; Alireza Assareh; Sadefg Nasri; Mohammad Armand (مجله علوم روانشناختی, 2023)
Background: Critical thinking is defined as the art of analyzing and evaluating thinking along with a review to correct it. Critical thinking is one of the basic needs of human life for decision-making, selection, and deep understanding of various issues. There is a research gap regarding the possible role of analytical literacy and computer literacy in predicting critical thinking with regard to the gender variable. Aims: This study was conducted to predict critical thinking through computer and analytical literacy with the mediating role of gender in second-year high school students of Gilan province. Methods: Research method was descriptive correlation type and the statistical population included second-year high school students of Gilan province in the first half of the academic year 2019-2020. The statistical sample included 384 people (191 girls and 193 boys) who were randomly selected in person and virtual. Data collection tools included critical thinking questionnaire (Ricketts', 2003) and researcher-made computer and analytical literacy questionnaires. The data were analyzed using hierarchical regression, multivariate regression, and Z-test using SPSS software version 26, and a significance level of 0.05 was considered to test the hypotheses. Results: The results showed that the effect of analytical literacy and computer literacy on students' critical thinking is positive and significant and explains 43% of its changes. Also, multiple relationships between analytical literacy and computer literacy with critical thinking have been stronger in male students than in female students. Conclusion: According to the obtained findings, it seems that Critical thinking in students can be predicted by the variables of analytical literacy and computer literacy according to the role of gender